Penerapan Data Mining Menggunakan Algoritma C4.5 Dalam Memprediksi Tingkat Perceraian Kecamatan Kuranji Kota Padang Berbasis Website - Karmila Hannum; Yusli Yenni (Riset Sinergi Indonesia (RISINDO), 2025)
Divorce is one of the social problems that continues to increase and affects family harmony as well as children’s psychological development. Based on data from the Religious Court of Kuranji District, Padang City, during 2022–2024, divorce cases experienced fluctuations with a significant increase. This issue encourages the need for a system that can help predict divorce rates as a basis for decision-making. This study applies data mining using the C4.5 algorithm to classify the factors causing divorce, such as continuous disputes, physical abandonment, economic issues, and other factors. The C4.5 algorithm was chosen because it can generate decision tree models that are easy to interpret and effective for prediction. This research produced a web-based system that provides predictive information about divorce rates, which is expected to assist the religious court and government in anticipating and reducing divorce cases. The results show that the implementation of the C4.5 algorithm can provide more accurate solutions in predicting divorce rates by utilizing available data and has the potential to be a useful decision support tool.